Case Report: Christianson Syndrome Caused by SLC9A6 Mutation: From Case to Genotype-Phenotype Analysis - Lan, Yueyun; Yi, Sheng; Li, Mengting; Wang, Jinqiu; Yang, Qi; Yi, Shang; Chen, Fei; Huang, Limei; Ruan, Yiyan; Shen, Yiping; Luo, Jingsi; Qin, Zailong (Frontiers in Genetics, 2021)
Christianson syndrome (CS) is an X-linked neurodevelopmental syndrome characterized by microcephaly, epilepsy, ataxia, and severe generalized developmental delay. Pathogenic mutations in the SLC9A6 gene, which encodes the Na+/H+ exchanger protein member 6 (NHE6), are associated with CS and autism spectrum disorder in males. In this study, whole exome sequencing (WES) and Sanger sequencing revealed a novel de novo frameshift variant c.1548_1549insT of SLC9A6 in a 14-month-old boy with early-onset seizures. According to The American College of Medical Genetics and Genomics (ACMG) / the Association for Molecular Pathology (AMP) guidelines, the variant was classified as pathogenic. The proband presented with several core symptoms of typical epilepsy, including microcephaly, motor delay, distal muscle weakness, micrognathia, occasional unprovoked laughter, swallowing and speech difficulties. Electroencephalography (EEG) showed spikes-slow waves in frontal pole, frontal, anterior temporal and frontal midline point areas. Gesell development schedules (GDS) indicated generalized developmental delay. We also summarized all the reported variants and analyzed the correlation of genotype and phenotype of CS. Our study extends the mutation spectrum of the SLC9A6 gene, and it might imply that the phenotypes of CS are not correlated with SLC9A6 genotypes.